2012
DOI: 10.1039/c2jm16487f
|View full text |Cite
|
Sign up to set email alerts
|

Solvent and polymer matrix effects on TIPS-pentacene/polymer blend organic field-effect transistors

Abstract: We report on a systematic study of solvent and polymer matrix effects on the phase segregation behavior of 6,13-bis(triisopropylsilylethynyl) pentacene (TIPS-pentacene) blends incorporated into two different amorphous polymer matrices, poly (a-methyl styrene) and poly (triarylamine), and using two solvents, chlorobenzene and tetralin. Optical microscopy, X-ray diffraction analyses, and optical absorption measurements are used to evaluate the film morphology, crystallinity, and optical density, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
107
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 27 publications
3
107
1
Order By: Relevance
“…[40] For these reasons, a variety of solvents and solvent-blends have been explored previously in organic electronics as a simple manufacturing approach to morphological and hence electrical performance optimisation. [15] We were able to significantly improve the performance and device-to-device parameter distribution of the C8-BTBT:C16IDT-BT:C60F48 blend OTFTs by using a solvent mixture composed of tetralin and CB (tetralin:CB). As with the single solvent formulations, we investigated both the impact of dopant concentration as well as the C8-BTBT loading ratio.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[40] For these reasons, a variety of solvents and solvent-blends have been explored previously in organic electronics as a simple manufacturing approach to morphological and hence electrical performance optimisation. [15] We were able to significantly improve the performance and device-to-device parameter distribution of the C8-BTBT:C16IDT-BT:C60F48 blend OTFTs by using a solvent mixture composed of tetralin and CB (tetralin:CB). As with the single solvent formulations, we investigated both the impact of dopant concentration as well as the C8-BTBT loading ratio.…”
mentioning
confidence: 98%
“…[4] [13] [14] Small molecules are well-known for their high charge carrier mobilities due to their high crystallinity, however they are difficult to process from a solution-phase. [15] [16] [17] Polymers, on the other hand, offer superior solution-processing qualities and produce uniform thin-films, but they are generally characterised by lower charge carrier mobility values. [17] [18] Blending small molecules with polymers has been shown to combine the high electrical performance traditionally associated with the small molecule with the superior filmforming attributes of the polymer, leading to semiconducting systems that combine the best of both worlds.…”
mentioning
confidence: 99%
“…As has been proposed in literature, a viable way to address these issues is the use of small molecules:polymer blend systems [16,17]. In such cases, the good film forming properties of the polymers can be efficiently combined with the high charge carrier mobility found in crystalline organic semiconductors and thus provide better performance consistency as well as enhanced mobilities.…”
Section: Introductionmentioning
confidence: 99%
“…This was the starting point for our research. In this study, we have demonstrated that the use of o-xylene and 1,2-dichlorobenzene (DCB) as major and minor solvents along with the addition of poly(α-methylstyrene) (PAMS) as a binder for TIPS-pentacene [7] leads to a more uniform crystallization in the droplets as compared to other common solvents compatible to a large area Roll-to-Roll (R2R) processing.…”
Section: Introductionmentioning
confidence: 99%
“…Although a lot of research has been published on the advances of using printed TIPS-pentacene in which different research groups have built organic field-effect transistors (OFET) with mobility in the saturation regime greater than 1 cm 2 /Vs [5,6], most organic semiconductor (OSC) circuitry is still based on evaporated pentacene due to the reproducibility and homogeneity of the results. This is due to the inherent problem that plagues TIPS-pentacene and other such small molecule semiconductors that the poor control of the phase distribution and morphology leads to a wider disparity in the device-to-device performance [7].…”
Section: Introductionmentioning
confidence: 99%